2022
DOI: 10.1007/s12024-021-00448-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of deceased and quality of death certificates for cases subjected to Indonesia’s management of the dead protocol for bodies with COVID-19

Abstract: The COVID-19 pandemic has significantly impacted many aspects of life, including death care. International and national protocols have been implemented for the management of the dead. This study aims to determine the characteristics of decedents managed according to COVID-19 protocols in Indonesia and the quality of their death certificates. This study uses a descriptive, cross-sectional design. Secondary data of deaths with COVID-19 were taken from hospital death registries, medical records, and death certifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In general, it is difficult to obtain characteristics of infected patients and clinical observations of patients at the population level in the early stages of a pandemic [ 34 ]. Thus, determining the exact cause of death is essential for planning prevention and control measures, especially during a pandemic that requires rapid public action [ 24 ]. In addition, high-quality death certificates containing correct information enable national health authorities to collect timely and accurate information to assist in the assessment and management of infectious diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is difficult to obtain characteristics of infected patients and clinical observations of patients at the population level in the early stages of a pandemic [ 34 ]. Thus, determining the exact cause of death is essential for planning prevention and control measures, especially during a pandemic that requires rapid public action [ 24 ]. In addition, high-quality death certificates containing correct information enable national health authorities to collect timely and accurate information to assist in the assessment and management of infectious diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it was difficult to accurately determine the number of deaths associated with COVID-19 due to the limited availability of diagnostic tests in the early stages of the pandemic [ 21 , 22 ]. In addition, issues related to the classification of deaths have been raised, as India lacks complete death certificates [ 23 ], and Indonesia is known to have under-reported deaths due to incomplete certification of deaths [ 24 ]. A study also identified many errors related to causes of death on death certificates in Iran [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This distribution is consistent with other studies which revealed that advanced age is a significant risk factor for death and is true for novel coronavirus disease. [22][23][24] 25 -Grade V error (underlying cause of death was incorrectly attributed or placed in an improper sequence, n=176, 87%)…”
Section: Discussionmentioning
confidence: 99%
“…31 A similar finding was noted in the Indonesian study on the quality of COVID-19 death certificates. 22 In the present study wrong terminology like "COVID", "COVID pneumonia", "COVID +ve", and "coronavirus" were used instead of COVID-19 and novel coronavirus disease. It has been made clear by COVID-19 guidelines for death certification and coding that only COVID-19 is an official terminology to be used for all certification of this cause of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation